Fresh stirrings among statisticians: statistical commentary - Godfrey Keith (Sciendo, 2016)
For some years there has been unrest in the statistical world regarding the use of the p-value. It has been indicated that the significance of p-values is open to question, which therefore reduces the ability to measure the strength of evidence. This paper examines the use and misuse of the p-value and recommends consideration in its application.